Subject index - The Editors, - (Nordic Archaeological Abstracts - NAA, 1989)
In order to simplify the use of the index, the detail entries have been grouped under main entries as far as possible, for example Plough under Agriculture. In most cases reference is given from a detail entry to the main heading. In the concise abstracts all important subjects cannot always be mentioned; consequently some entries in the index will not be found in the corresponding abstract but refer to the original publication. General surveys and general catalogues are not mentioned in all relevant entries ( Graves, Weapons, etc.); they are to be found under SURVEYS and CATALOGUES